Analisis Praktik Murabahah Emas pada Bank Syariah di Indonesia Berdasarkan Tinjauan Hukum Fikih Muamalah - Marianti, Dina Juni; Rasyida, Zulfa; Utami, Ema (TAJDID, 2021)
This study examines the concept of investing or saving gold in Islamic banks, which is carried out with the murabahah (buying and selling) financing model. The researcher found that there were problems in the murabahah contract and the gold payment mechanism carried out through fixed monthly installments. This study uses a comparative legal analysis method used by Islamic banks, the DSN MUI fatwa, and a review of fiqh muamalah according to the number of scholars on the other. To explain this, the researcher used a qualitative descriptive method with a muamalah fiqh approach. Through this approach, the researcher suggests practicing according to the Shari'a. The researcher found that there were differences of opinion among scholars regarding the concept of murabahah and gold installments, where the majority of scholars forbade it. This article presents the concept of gold murabahah at Bank Mandiri Syariah to evaluate the concept of saving gold with a gold murabahah contract at Islamic banks. This research contributes to the analysis aspect of saving gold in Islamic banks based on the fiqh muamalah review.